In vitro selection and characterization of new probiotic candidates from table olive microbiota. - Cristian Botta; Tomaz Langerholc; Avrelija Cencič; Luca Cocolin (PLoS ONE)
To date, only a few studies have investigated the complex microbiota of table olives in order to identify new probiotic microorganisms, even though this food matrix has been shown to be a suitable source of beneficial lactic acid bacteria (LAB). Two hundred and thirty eight LAB, belonging to Lactobacillus plantarum, Lactobacillus pentosus and Leuconostoc mesenteroides species, and isolated from Nocellara Etnea table olives, have been screened in this survey through an in vitro approach. A simulation of transit tolerance in the upper human gastrointestinal tract, together with autoaggregation and hydrophobicity, have been decisive in reducing the number of LAB to 17 promising probiotics. None of the selected strains showed intrinsic resistances towards a broad spectrum of antibiotics and were therefore accurately characterized on an undifferentiated and 3D functional model of the human intestinal tract made up of H4-1 epithelial cells. As far as the potential colonization of the intestinal tract is concerned, a high adhesion ratio was observed for Lb. plantarum O2T60C (over 9%) when tested in the 3D functional model, which closely mimics real intestinal conditions. The stimulation properties towards the epithelial barrier integrity and the in vitro inhibition of L. monocytogenes adhesion and invasion have also been assessed. Lb. plantarum S1T10A and S11T3E enhanced trans-epithelial electrical resistance (TEER) and therefore the integrity of the polarized epithelium in the 3D model. Moreover, S11T3E showed the ability to inhibit L. monocytogenes invasion in the undifferentiated epithelial model. The reduction in L. monocytogenes infection, together with the potential enhancement of barrier integrity and an adhesion ratio that was above the average in the 3D functional model (6.9%) would seem to suggest the Lb. plantarum S11T3E strain as the most interesting candidate for possible in vivo animal and human trials.